CD56 Expression in Papillary Thyroid Carcinoma Is Highly Dependent on the Histologic Subtype: A Potential Diagnostic Pitfall. Issue 5 (1st May 2022) - Cho, Uiju; Kim, Yourha; Jeon, Sora; Jung, Chan Kwon
Abstract : Loss of CD56 expression has been regarded as a diagnostic marker of papillary thyroid carcinoma (PTC). However, certain variants of PTC can aberrantly express CD56. Using a digital image analysis tool, we evaluated H-scores of CD56 immunostaining in 216 thyroid tumors. The H-score of the CD56 of all PTCs was lower than that of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) ( P <0.001). The H-scores of CD56 were lower in classic PTC, the infiltrative follicular variant, and the diffuse sclerosing variant than in other PTC variants ( P <0.001), whereas the H-scores were higher in tall cell variant, Warthin-like variant, and cribriform-morular variant than in classic PTC ( P <0.001). The optimal cutoff value of H-scores for the CD56 expression was 180 for differentiating the NIFTP from the follicular adenoma and 30 for the differential diagnosis of NIFTP and infiltrative follicular variant PTC. CD56 expression is predominantly lost in classic and infiltrative follicular variants of PTCs and more preserved in the other histologic subtypes of PTC and NIFTP. CD56 is particularly useful for differentiating PTC from follicular-pattern thyroid neoplasms, but the aberrant expression in uncommon variants of PTC could be a diagnostic pitfall.